Academic optimism at the Distinguished Students (Journal Of Educational and Psychological Researches, 2023)
Students at secondary school, particularly at the beginning of their academic lives face many difficulties and problems in various psychological, educational, and social fields, which require them to make many decisions and solve problems that may confront them while maintaining their optimism and positivity for life in general and for academic life in particular. Thus, the current study aims to investigate the academic optimism of distinguished students and identify the differences in academic optimism in terms of gender. The researcher applied the scale to a sample of (336) students, (145) males, and (191) females, who were chosen randomly from distinguished schools. In order to achieve the research objectives, the researcher adopted the academic optimism scale (McKinnon, 2012), which consists of (27) items distributed over three domains (collective teacher effectiveness, trust of faculty members in parents and students, and academic focus). The results showed that the distinguished students have academic optimism. There are no statistically significant differences in terms of gender. The researcher came up with a number of conclusions, recommendations, and suggestions. The teaching staff should spread a culture of academic optimism among students